(untitled) (Rudarsko-geološko-naftni zbornik, 2023)
Despite its importance, sea surface paleoproductivity of the western Savu Strait is not well studied. Results from previous studies at the nearby Southwest Sumba and Sumba Strait might not be applicable due to the oceanographic difference. Foraminiferal proxies from gravity core ST10 were applied to generate sea surface paleoproductivity and thermocline depth reconstruction. Foraminiferal Accumulation Rate and Benthic Foraminiferal Accumulation Rate were used as paleoproductivity proxies while the thermocline dwellers’ relative abundance was applied as the thermocline depth proxy. This study suggested paleoproductivity increase during the Last Glacial Maximum (LGM)– 16 ka BP and Holocene (after 11.65 ka BP) in the western Savu Strait. Thermocline depth was relatively shallower during the LGM–Last Deglaciation and became deeper afterwards. Paleoproductivity increase at LGM– 16 ka BP was caused by the Australian-Indonesian winter monsoon (AIWM)-like condition, characterized by intense coastal upwelling while the Holocene paleoproductivity increase was related to the abrupt rainfall increase which enhanced terrestrial/riverine input. Thermocline depth variability in the western Savu Strait is in-phase with thermocline depth variability in the Java upwelling region, characterized by a shallower thermocline during the LGM–Last Deglaciation (before 11.65 ka BP) and a deeper thermocline during the Holocene (after 11.65 ka BP). This thermocline depth shifting indicates a strong Australian-Indonesian Monsoon (AIM) influence on the paleoceanography of the western Savu Strait since LGM.